Recursion relations for a class of generalized eliptic integrals - Glasser, M. L.; Kalla, S. L. (Revista Técnica da Faculdade de Engenharia da de Zulia)
Our purpose in this note is to provide a number of recursión formulas for RÂµ (véase archivo PDF), so that the numerical results can be extended to arbitrary parameter values.